IDENTIFIKASI KESUBURAN TANAH TANAMAN KELAPA SAWIT PADA LAHAN PASCA PENAMBANGAN EMAS DESA ROBAN KECAMATAN SINGKAWANG TENGAH - Saddam Gusty Mandala; Asrifin Aspan; Rita Hayati (Perkebunan dan Lahan Tropika, 2021)
Research was conducted on post-mining land the gold that has been planted with oil palm. This research is motivated by post-mining land conditions, the fertility of the ground to, oil palm plantations and the process of implementation of aquaculture activities. The purpose of research is to identify the soil fertility status of oil palm trees and prepare advice for nutrient management (fertilizer recommendation). This study used survey method with descriptive and comparative approach undertaken by soil sampling in the field on four objects observation at the sites. Parameter study soil bulk density, soil pH, N-total, P-available, K-available, cation exchange capacity, organic C, and Base saturation. The basis for determining the criteria used is the criterion of soil fertility Land Research Center in 1983. The results showed that the pH criteria sour, total nitrogen, available phosphorus, available potassium, organic C, cation exchange capacity and base saturation low to very low. Nitrogen fertilizer recommendations, P2O5 and K2O needs to be added to plant oil palm on the location of the study as follows: C1 is 1.98 kg urea / tree / year, 0.98 kg of SP-36 / tree / year, 1.82 kg KCl / tree / year. C2 is 1.98 kg urea / tree / year, 1.39 kg of SP-36 / tree / year, 1.87 kg KCl / tree / year. C3 is 1.96 kg urea / tree / year, 1.15 kg of SP-36 / tree / year, 0.89 kg KCl / tree / year. C4 is 1.95 kg urea / tree / year, 0.83 kg of SP-36 / tree / year, 0.05 kg KCl / tree / year.Keywords: Soil Fertility, Land Used Gold Mining, Oil Palm Plant